PENGARUH PANDEMIK COVID-19 TERHADAP GERAKAN TRANSPORTASI DI JABODETABEK - Sylvira Ananda Azwar; Yusuf Abdurrohman (LOGISTIK, 2021)
The research method used is by distributing questionnaires to respondents who are Jabodetabek people. The analyzes carried out were analysis of travel destinations, analysis of origin and destination areas, and analysis of modal choices during the Covid-19 pandemic to large-scale social restrictions (PSBB). The results of distributing questionnaires with 150 respondents stated that there was a decrease in movement in Jabodetabek by a percentage of 38%. The decrease occurred in 36% of recreational trips, 34% of education, 28% of work and 23% of social activities. The rate of increase in private vehicles is 25%. From these results it can be stated that the Covid-19 pandemic has an influence on the movement of people and transportation in Jabodetabek. Some suggestions in this regard are increasing travel supervision and tightening health protocols in each mode, as well as improving services on public transportation when trips have returned to normal by adding schedules and fleets to public transportation to reduce congestion so as to maintain health protocols in public transport.